2021
DOI: 10.1038/s41467-021-24754-w
|View full text |Cite
|
Sign up to set email alerts
|

Auditory input enhances somatosensory encoding and tactile goal-directed behavior

Abstract: The capacity of the brain to encode multiple types of sensory input is key to survival. Yet, how neurons integrate information from multiple sensory pathways and to what extent this influences behavior is largely unknown. Using two-photon Ca2+ imaging, optogenetics and electrophysiology in vivo and in vitro, we report the influence of auditory input on sensory encoding in the somatosensory cortex and show its impact on goal-directed behavior. Monosynaptic input from the auditory cortex enhanced dendritic and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Simultaneous audio-tactile stimulation can improve reaction times ( Sperdin et al, 2009 ; Godenzini et al, 2021 ) and stimulus detection ( Schürmann et al, 2004 ; Gillmeister and Eimer, 2007 ; Ro et al, 2009 ), and increase perceived loudness ( Gillmeister and Eimer, 2007 ; Yarrow et al, 2008 ). These interactions have been shown to occur in a frequency-dependent manner ( Ro et al, 2009 ; Tajadura-Jiménez et al, 2009 ; Wilson et al, 2010a , b ), with the largest perceptual improvements reported when the frequencies of the auditory and vibrotactile stimuli are closely matched ( Ro et al, 2009 ; Wilson et al, 2010b ).…”
Section: Perceptual Consequences Of Interactions Between Auditory And...mentioning
confidence: 99%
See 4 more Smart Citations
“…Simultaneous audio-tactile stimulation can improve reaction times ( Sperdin et al, 2009 ; Godenzini et al, 2021 ) and stimulus detection ( Schürmann et al, 2004 ; Gillmeister and Eimer, 2007 ; Ro et al, 2009 ), and increase perceived loudness ( Gillmeister and Eimer, 2007 ; Yarrow et al, 2008 ). These interactions have been shown to occur in a frequency-dependent manner ( Ro et al, 2009 ; Tajadura-Jiménez et al, 2009 ; Wilson et al, 2010a , b ), with the largest perceptual improvements reported when the frequencies of the auditory and vibrotactile stimuli are closely matched ( Ro et al, 2009 ; Wilson et al, 2010b ).…”
Section: Perceptual Consequences Of Interactions Between Auditory And...mentioning
confidence: 99%
“…In addition to the higher-level cortical association areas implicated in the representation of peripersonal space, multisensory signals have been found to converge throughout the cortex, including in auditory, somatosensory and visual early cortical areas (reviewed in Ghazanfar and Schroeder, 2006 ; Meijer et al, 2019 ). Thus, responses to auditory stimulation in somatosensory cortical areas have been reported in both human fMRI ( Liang et al, 2013 ; Pérez-Bellido et al, 2018 ; Rahman et al, 2020 ) and magnetoencephalography studies ( Lütkenhöner et al, 2002 ), as well as in single-neuron measurements in monkeys ( Zhou and Fuster, 2004 ) and mice ( Carvell and Simons, 1986 ; Zhang et al, 2020 ; Godenzini et al, 2021 ). More attention has been paid, however, to the way that other sensory modalities affect activity in the auditory cortex, with somatosensory influences demonstrated using a range of methods and in several different species ( Foxe et al, 2002 ; Fu et al, 2003 ; Brosch et al, 2005 ; Kayser et al, 2005 ; Schürmann et al, 2006 ; Lakatos et al, 2007 ; Lemus et al, 2010 ; Iurilli et al, 2012 ; Nordmark et al, 2012 ; Hoefer et al, 2013 ; Rao et al, 2014 ; Lohse et al, 2021 ).…”
Section: Interactions Between Auditory and Somatosensory Inputs In Th...mentioning
confidence: 99%
See 3 more Smart Citations